Encapsulation of Bacillus salmalaya 139SI using double coating biopolymer technique. (1st January 2019) - Vejan, P.; Abdullah, R.; Khadiran, T.; Ismail, S.
Abstract: Sustainable crop production for a rapidly growing human population is one of the current challenges faced by the agricultural sector. However, many of the chemical agents used in agriculture can be hazardous to humans, non‐targeted organism and environment. Plant growth promoting rhizobacteria have demonstrated a role in promoting plant growth and health under various stress conditions including disease. Unfortunately, bacterial viability degrades due to temperature and other environmental factors (Bashan et al ., Plant Soil 378 : 1–33, 2014). Encapsulation of bacteria into core‐shell biopolymers is one of the promising techniques to overcome the problem. This study deals with the encapsulation of Bacillus salmalaya 139SI using simple double coating biopolymer technique which consist of brown rice protein/alginate and 0·5% low molecular weight chitosan of pH 4 and 6. The influence of biopolymer to bacteria mass ratio and the chitosan pH on the encapsulation process, physic‐chemical, morphology and bioactivity properties of encapsulated B. salmalaya 139SI have been studied systematically. Based on the analysis of physico‐chemical, morphology and bioactivity properties, B. salmalaya 139S1 encapsulated using double coating encapsulation technology has promising viability pre‐ and postfreeze‐drying with excellent encapsulation yields of 99·7 and 89·3% respectively. Significance and Impact of the Study: The need of a simple yet effective way of encapsulating plant growth promoting rhizobacteria is crucial to further improve their benefits to global sustainable agriculture practice. Effective encapsulation allows for protection, controlled release and function of the micro‐organism, as well as providing a longer shelf life for the product. This research report offers an innovative yet simple way of encapsulating using double coating technology with environmentally friendly biopolymers that could degrade and provide nutrients when in soil. Importantly, the bioactivity of the bacteria is maintained upon encapsulation.